Identification of fossil worm tubes from Phanerozoic hydrothermal vents and cold seeps. (16th February 2019) - Georgieva, Magdalena N.; Little, Crispin T. S.; Watson, Jonathan S.; Sephton, Mark A.; Ball, Alexander D.; Glover, Adrian G.
Abstract : One of the main limitations to understanding the evolutionary history of hydrothermal vent and cold seep communities is the identification of tube fossils from ancient deposits. Tube-dwelling annelids are some of the most conspicuous inhabitants of modern vent and seep ecosystems, and ancient vent and seep tubular fossils are usually considered to have been made by annelids. However, the taxonomic affinities of many tube fossils from vents and seeps are contentious, or have remained largely undetermined due to difficulties in identification. In this study, we make a detailed chemical (Fourier-transform infrared spectroscopy and pyrolysis gas-chromatography mass-spectrometry) and morphological assessment of modern annelid tubes from six families, and fossil tubes (seven tube types from the Cenozoic, 12 Mesozoic and four Palaeozoic) from hydrothermal vent and cold seep environments. Characters identified from these investigations were used to explore for the first time the systematics of ancient vent and seep tubes within a cladistic framework. Results reveal details of the compositions and ultrastructures of modern tubes, and also suggest that two types of tubes from ancient vent localities were made by the annelid family Siboglinidae, which often dominates modern vents and seeps. Our results also highlight that several vent and seep tube fossils formerly thought to have been made by annelids cannot be assigned an annelid affiliation with any certainty. The findings overall improve the level of quality control with regard to interpretations of fossil tubes, and, most importantly, suggest that siboglinids likely occupied Mesozoic vents and seeps, greatly increasing the minimum age of the clade relative to earlier molecular estimates.